The issue of thermal comfort of medical clothing in the operating room - Abreu, Isabel (2017)
Medical clothes have the primary function of protection. However this function must be correlated with a good comfort experience to the user. The comfort is a very important issue, since professionals are exposed to stress situations that can influence, negatively, their performance work. More specific, thermal comfort plays a crucial role for the best performance of OR medical clothing, involving heat regulation and mass transfer between a clothed body and the environment, once clothing is the interface between body and environment. The aim of this work was to study the behavior of thermal properties of surgical scrub and clean air suits A comparison was made between this two types of clothing using Alambeta equipment, for stationary thermal properties and a Thermal Manikin, to allow the analysis of dynamic thermal properties, such as heat flux and thermal insulation. It was found that clothing thermal insulation is statistically different, showing that the difference between suits may will perceived by the user.